The prevalence of depression among diabetic patients in Sub-Saharan Africa and its impact on their glycaemic control: a systematic review - Chirewa, Blessing M.; Nyashanu, Mathew; Barnard, Adam; Ibe, Jacinta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Type 2 diabetes poses a major global health challenge, especially in Sub-Saharan Africa, where healthcare systems are often weak and the condition’s prevalence is increasing. A common but frequently overlooked complication in Sub-Saharan Africa is depression, which often goes undiagnosed and untreated. Depression is often associated with poor adherence to medication and self-care routines, leading to adverse outcomes like poor glycaemic control. Recognising how common depression is among diabetes patients and understanding the factors affecting glycaemic management in this region are crucial steps toward creating targeted interventions to improve type 2 diabetes mellitus treatment and enhance patients’ quality of life. The study aimed to determine how common depression is among patients with type 2 diabetes mellitus in Sub-Saharan Africa and to examine the impact of depression on their glycaemic control. We conducted a comprehensive search of PubMed, PsycINFO, Scopus, ScienceDirect, Cochrane Library, Embase, Medline, and Google Scholar for studies on depression in individuals with type 2 diabetes mellitus in Sub-Saharan Africa and its impact on glycaemic control. Only peer-reviewed, English-language primary research articles published from January 2014 to January 2024 were eligible. Two reviewers independently selected and evaluated the articles using the Critical Appraisal Programme Tool and extracted data in accordance with preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The review analysed 12 studies involving 3,709 participants across eight Sub-Saharan African countries. The reported rates of co-morbid depression varied, likely due to differences in sample size rather than regional factors. Five studies included gender data, showing a significant association between depression and being female. Glycaemic control rates ranged from 11.9% to 89.7%. Overall, the results demonstrated a strong link between depression among type 2 diabetes mellitus patients and poor glycaemic control (HbA1c >7%), although some studies found no such connection. The study revealed a high overall rate of comorbid depression among patients with type 2 diabetes in Sub-Saharan Africa. It also highlighted that diagnosing depression in these patients is usually associated with poor glycaemic control. Therefore, public health policymakers in the region should develop targeted strategies for screening, diagnosing, and treating depression in individuals with type 2 diabetes.